Ten non-native Chinese speakers from UMP excelled in their Mandarin Proficiency International Test - UMP, PNC (Pejabat Naib Canselor, 2016)
Ten non-native Chinese speaking University Malaysia Pahang (UMP) undergraduates scored outstanding marks in their Mandarin Proficiency International Test which was announced on January 15, 2016.